Utilização de atividades contextualizadas: uma perspectiva de aprimoramento de competências para o ensino da química de polímero- PET - Oliveira, Marcio Aparecido de (Universidade Federal de São Carlos, 2016)
This work is the application of qualitative methodology in context, related to the packaging of carbonated drinks: the plastic bottles. These bottles have as raw material for manufacturing the monomer, Terephthalic acid, non-renewable resource, stemming from oil and ethylene glycol, Polymer [poly (ethylene terephthalate)], material that makes up this container used by society. This research was contextualized, using as instrument packing, Polymer, Topic-related content studied in organic chemistry, specifically, in the third year of high school, as the Basic Curricular Component orientation used in the State of Minas Gerais. And, to encourage participants to research a better interaction and participation in chemistry lessons, sought to improve the prior knowledge of them, regarding to the topic in question, encouraging them to apply it in later studies and in everyday life. This subject arouse the interest of students, through contextualized activities, so that they could learn the competences on the aspects of the chemistry of polymers which form the bottle with a focus on Science, technology, society and environment, to encourage participation in the classroom, as well as in their sequential studies to be applied in practice, proposing extra classes activities. The work was developed with the research question: how activities in context can highlight the students ' learning of the third year of high school chemistry aspects of polymers? Due to concerns of students on how the formulas and chemical reactions are worked, i.e. without contextualization. Thus, it was decided to make use of a new sequence. To give students direct contact with environmental problems to experience the situation, disposal and recycling, and awaken the interest of students by teamwork. In the course of the activities, sought to teach formulas and the reactions, leading them to an attempt at assimilation of the contents taught in the classroom with the bottle. And, consequently, provide them with learning the chemistry of polymers, using the theory and the practice for which ownership of competences and break into new concepts. So, the following issues were raised: the improper disposal of bottles and the environmental consequences that these cause, when they accumulate in galleries, slopes of rivers and parts of cities. During the research, participants conducted field study on the path from the House to the school grounds. In this way, the students were able to observe the environment around you, conduct experiments in two steps in the science lab and make objects of plastic bottles. In addition, aware students other shifts regarding the improper disposal, recycling, reuse of packing the polymerization reaction and also exposed the learning acquired during the search, as they provided an enriching exchange of experiences
Keywords: Contextualização; Competências; Polímeros; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA